Bāṃlā sāhitye Mohitalāla - Khān, Ājahārauddīna, 1930- (Jijñāsā, 1978)
Study on the literary genius of the Bengali litterateur Mohitlal Majumdar, 1888-1952; includes an annotated bibliography of Majumdar's works.